Atypical metanephric adenoma: Shares similar histopathological features and molecular changes of metanephric adenoma and epithelial-predominant Wilms’ tumor - Yin, Xiaoxue; Zhang, Xingming; Pan, Xiuyi; Tan, Junya; Zheng, Linmao; Zhou, Qiao; Chen, Ni (Frontiers in Oncology, 2022)
Background: Metanephric adenomas (MAs) are rare, benign renal tumors. Wilms’ tumors (WTs) are malignant embryonic tumors that originated from nephrogenic blastemal cells. However, some tumors have similar morphology to both MA and epithelial-predominant WT, which makes differential diagnosis difficult. We aimed to analyze the morphological, immunophenotypic and molecular changes in overlapping cases to explore their attribution. Methods and Results: Twenty MAs, ten WTs, and nine cases with MA/WT overlapping histological features were studied. Twenty tumors demonstrated the typical morphological spectrum of MA with high cellularity and were composed of tightly packed small, uniform, round acini with a lower Ki67 index. Almost all MAs (94.7%, 18/19) were detected with BRAF V600E mutation. The ten WTs were epithelial-predominant WTs with glands, rosettes and glomerular structures, which also showed a higher Ki-67 index (up to 60%), invasive growth patterns, and a lack of BRAF mutation. However, the other nine overlapping cases showed two components: typical MA-like areas and epithelial WT-like areas. The cells of the WT-like areas were tubular, columnar and showed marked cytological atypia, with a Ki-67 proliferative index of up to 30%. The immunophenotype of these overlapping lesions was not significantly different from that of typical MA and they positively expressed WT1 and CD57. The BRAF V600E mutation was detected in both WT-like and MA-like areas in nine overlapping tumors. The follow-up data of 31 patients were analyzed, with a median follow-up time of 66 months (range, 8-45 months). Even though most patients with WT underwent radiotherapy or chemotherapy after surgery, two died, and one had liver metastasis. No MA or overlapping cases showed any evidence of recurrence or metastasis after surgery. Conclusions: The molecular changes in tumors with overlapping morphological features were the same as those of typical MA; thus, we think that these tumors should be classified as MA and further called atypical MA. It is important to note that atypical MA is not a neglected subtype of MA. It possesses different histological morphology and a higher Ki-67 index but has the common imaging characteristics, immunophenotype and gene expression as typical MA, and patients usually have a good prognosis.